Real earnings management activities prior to bond issuance - Cristhian Mellado-Cid; Surendranath R. Jory; Thanh Ngo (BRQ Business Research Quarterly, 2017)
We examine real activities manipulation by firms prior to their debt issuances and how such manipulation activities affect bond yield spreads. We find that bond-issuing firms increase their real activities manipulation in the five quarters leading to a bond issuance. We document an inverse association between yield spread and pre-issue real activities manipulation, i.e., firms engaged in abnormally high levels of real activities manipulation are associated with subsequent lower cost of debt."
Keywords: 650; Real activities manipulation; Debt issues; Earnings management